Creatine - cutting through the myths (Peak Performance, 2002)
Creatine is a performance-enhancing supplement that has been in the news for a decade or more. Famous athletes who have used it include Linford Christie and Sally Gunnell. The general consensus of early scientific opinion was that it boosted short-term performance, but more recently researchers have discovered that it aids endurance athletes as well and even helps produce a final kick at the end of a race - both these benefits are discussed in this report. Inevitably, of course, there have been detractors: creatine makes you gain weight, they say, or it dilutes potassium and calcium in the muscles, or it causes cramping. The purpose of this special report is to sort out the facts from the fiction about creatine. It reviews the scientific research as well as the evidence of practical athletes to tell you what creatine actually does (and doesn't) do, who should try it, how much to take, and how to gain the maximum performance boost. We have assembled quite a battery of experts on your behalf, including one of the world's leading authorities on the subject. After reading this report, you should have a clear idea of the benefits of creatine to your own performance. Finally, as a bonus, we offer at the end of this report an analysis of three other performance-boosting substances: HMB, caffeine and sodium bicarbonate.